Dampak Penggunaan Media Sosial Terhadap Pemahaman Agama Islam Siswa-Siswi Kelas IX A SMPN 1 Mantup Lamongan Tahun 2025 - Arifin, Zaenal; Syuhada'; Lathifatus Sun'iyah, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the impact of social media on the understanding of Islam among students at SMP Negeri 1 Mantup (Mantup 1 Public Junior High School). The rapid development of information technology, especially social media platforms such as YouTube, TikTok, Instagram, and WhatsApp, has become an inseparable part of teenagers' daily lives. On one hand, social media can serve as a tool for spreading religious information quickly and widely. On the other hand, unverified content or a mix of religious values and popular culture has the potential to cause misunderstandings about Islamic teachings. This research uses a qualitative approach through observation, interviews, and questionnaires distributed to students in grades VII to IX. The results show that while many students obtain religious information from social media, not all are able to distinguish between teachings based on authentic sources and personal opinions from influencers. Family environment and the role of religious teachers also influence students' level of understanding of Islamic teachings. The study concludes that social media has a dual impact both positive and negative on the understanding of Islam, depending on usage control as well as students’ digital and religious literacy skills. Keywords: Digital Literacy, Junior High School Students, Social Media, Understanding of Islam.